2020
DOI: 10.21037/atm-20-1960a
|View full text |Cite
|
Sign up to set email alerts
|

A new sarcopenia score prognostic for postoperative complications in hepatic alveolar echinococcosis: a multicenter retrospective study

Abstract: Background: Skeletal muscle depletion and excessive visceral adipose tissue have been shown to be independent risk factors for postoperative complications (PCs) in various diseases. However, their impact on surgical PCs in hepatic alveolar echinococcosis (HAE) is still unknown. Methods:We retrospectively reviewed the clinical data of HAE patients who underwent liver resection at our hospital between January 2008 and December 2018. We segmented skeletal muscle and adipose tissue and measured the area of skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Our previous multicenter research revealed that the sarcopenia was a predictive factor for postoperative complications in HAE patients undergoing liver resection and applied the severity of sarcopenia as a classifier to divide all patients into two groups for prediction. 28 In contrast, we retained the original sarcopenia score model to maintain a higher AUROC for the final nomogram for more accurate prediction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous multicenter research revealed that the sarcopenia was a predictive factor for postoperative complications in HAE patients undergoing liver resection and applied the severity of sarcopenia as a classifier to divide all patients into two groups for prediction. 28 In contrast, we retained the original sarcopenia score model to maintain a higher AUROC for the final nomogram for more accurate prediction.…”
Section: Discussionmentioning
confidence: 99%
“…We specifically collected plain abdominal CT images of all patients within one month before ELRA. Then, analyses of the image data and measurements of skeletal muscle and adipose tissue were performed at the level of the third lumbar vertebra with three-dimensional visualization software 28 (Mimics Interactive Medical Image Control System, Version 25.0, Materialize Company, Belgium). To divide out skeletal muscle and adipose tissue at the level of the third lumbar vertebra, skeletal muscle areas, which included the psoas, erector spinae, quadratus lumborum, transversus abdominis, and internal and external obliques, were quantified using −29 to 150 Hounsfield units (HU), and adipose tissue areas, which included the subcutaneous adipose tissue and visceral adipose tissue, were quantified using −190 to −30 HU.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation